Analisis Kelompok Acuan dan Atribut Produk terhadap Keputusan Pembelian Konsumen Tas Eiger pada Eiger Store Kota Sukabumi - Sansan Nurhasanah; Asep M Ramdan; Kokom Komariah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Purchasing decisions are often made by consumers based on their wants and needs. If the company is unable to fulfill it, it is likely to experience a decline in marketing the product. The purpose of this study was to determine the analysis of the reference group and product attributes to the purchasing decisions of eiger bag consumers in the eiger store in the city of sukabumi. The research method used in this study was to use a random sampling method, by distributing questionnaires as many as 87 respondents to eiger bag consumers. The analysis technique used in this study is to use multiple linear regression analysis techniques and coefficient of determination. To test the hypothesis in this study using partial statistical tests (t test) and simultaneous tests (Test f). The results of this study indicate that the reference group has a significant influence on purchasing decisions. Product attributes have a positive and significant influence on purchasing decisions. Simultaneously the reference group and product attributes have a positive and significant influence on purchasing decisions. Keywords: Reference Group, Product Attributes, Purchasing Decisions